Efficient Novel Synthesis of Bexaglifazolin and Its Glycol Salt With Minimal Impurities - Krishna Kilaru, Govinda G; Gutta, Madhusudan; Muppineedi, Veerababu; Pittu, Eswar Reddy; Gundekari, Sreedhar; Varkolu, Mohan (Synlett, 2025)
An efficient and novel process for the synthesis of the antidiabetic drug bexagliflozin using 5-iodo-2-chlorobenzoic acid as the starting material was described in detail to identify and eliminate the critical impurities that may form during the various steps of the synthetic process. The best reaction parameters, including temperature, stoichiometry, and reaction time, were systematically evaluated by analyzing the impurity profile at each stage of the synthesis. The process was carefully optimized to effectively control the formation of these critical impurities, which was a key factor in ensuring the successful synthesis of pure bexagliflozin.
Keywords: Diabetes mellitus; Sodium-glucose; Bexagliflozin; Glycol; impurities